New combination in Macrosamanea (Leguminosae-Mimosoideae) - Da Silva E Silva, Wanderson Luis; Morim, Marli Pires; Iganci, João Ricardo Vieira; Dos Santos, João Ubiratan Moreira (Phytotaxa, 2016)
As part of a revision of the genus Macrosamanea (Leguminosae), the name Macrosamanea discolor var. arenicola, based on Pithecellobium arenicola, is here raised to species. Taxonomic information, comparison with morphologically similar species, geographical distributions, phenological data and a conservation assessment are provided.